Effect Natural Disinfectants Compared to Selected Antibiotics and Plant Extracts on Staphylococcus Aureus and Escherichia Coli and their Resistance Levels - Ibrahim, Suaad Khalil (American Journal of Biomedicine and Pharmacy, 2025)
This study involved isolating Staphylococcus aureus and Escherichia coli from clinical samples. The bacteria were cultured on agar plates, and their antibacterial effects were tested using antibiotic disks and plant extracts. Five antibiotics were used: Ciprofloxacin showed the highest inhibition zones (29 mm for S. aureus, 27 mm for E. coli), while amoxicillin had the lowest. Two plants were used for extraction, and ethanolic extracts showed stronger effects than aqueous ones. The highest inhibition was observed with the 20% ethanol extract of Plant B (24 mm for S. aureus, 21 mm for E. coli). Vinegar alone showed moderate inhibition (17 mm for S. aureus and 15 mm for E. coli), but when mixed with the 20% ethanol extract of Plant B, the inhibition zones increased to 31 mm for S. aureus and 28 mm for E. coli. This combination was more effective than antibiotics alone. These results suggest that combining natural extracts with vinegar enhances antibacterial activity.